Locating Real-time Location of Perak Transit Buses and Determining its Estimation of Time of Arrival (ETA) at a Particular Bus Stop through the Development of Mobile Application on Android Platform - Wan Zakaria, Wan Afifi Zawawie; Arshad, Noreen Izza (Journal of Computing Technologies and Creative Content, 2016)
Creating an added value service to the current passengers and eventual users of public transports requires service providers to deal with and engage in the issues related to mobility, productivity, efficiency as well as security to vitally enhance the user’s travelling experience and improve the current public transportation scenario in Malaysia. Although with existing products and application, certain mentioned issues are not being satisfied by the developers. The project is centred on designing and developing a mobile application to track the real-time location of Perak Transit buses and determine the ETA of the bus at a specific bus stop. Through the use of technology and mobile application, the project and the development of the mobile application support the realization of ‘Perak Maju 2015’ by increasing the value of the public transportation sector in Perak, which should be considered a part of the development strategy. The application is built on Android platform using Rapid Application Development (RAD) method through the use of prototyping and utilizes the Global Positioning System (GPS) for the tracking purpose. The development of the project is focused on empowering the existing and prospective users of Perak Transit buses to obtain comprehensive set of information in making informed travelling decisions.